Neuron-Specific Enolase, S100 Calcium-Binding Protein B, and Heat Shock Protein 70 Levels in Patients With Intracranial Hemorrhage - Alatas, Omer Dogan; Gurger, Mehtap; Atescelik, Metin; Yildiz, Mustafa; Demir, Caner Feyzi; Ekingen, Evren; Acar, Ethem (Lippincott Williams & Wilkins, 2015)
The authors evaluated neuron-specific enolase (NSE), S100 calcium-binding protein B (S100B), and heat shock protein 70 (HSP 70) levels and their relationships with in-hospital mortality, Glasgow Coma Scale (GCS) scores, and National Institute of Health Stroke Scale (NIHSS) scores.In total, 35 patients older than 18 years were presented to our emergency department and were diagnosed with non-traumatic intracranial hemorrhage (ICH) and 32 healthy controls were included. Blood samples were drawn on days 0 and 5.S100 calcium-binding protein B and HSP levels were significantly higher in patients than in controls on days 0 and 5. Neuron-specific enolase levels were higher in patients than in controls on day 0, but there was no significant difference on day 5.S100 calcium-binding protein B was negatively correlated with GCS, whereas it was positively correlated with NIHSS and bleeding volume. There was also a negative correlation between NSE and GCS, but it was not statistically significant. In addition, no significant correlation was found in terms of bleeding volume or NIHSS. Heat shock protein 70 was negatively correlated with GCS and positively correlated with bleeding volume and NIHSS, but these results were not statistically significant. S100 calcium-binding protein B and HSP 70 levels were significantly higher in those who died compared with survivors. The areas under the curve of S100 B, NSE, and HSP 70 for mortality were 0.635, 0.477, and 0.770, respectively.Neuron-specific enolase, S100B, and HSP 70 levels are simple, inexpensive, and objective measures in cases of ICH. These tests can be used to support an assessment for screening ICH patients with clinical scoring systems, such as GCS and NIHSS.
Keywords: Spontaneous Intracerebral Hemorrhage; Traumatic Brain-Injury; Stress Gene; Expression; Markers; Hsp70; Shock; Patterns; S-100B; Damage